Intricacies Related To Retirement - Elijah, NG’ANG’A (Advances in Social Sciences Research Journal, 2018)
The relationship between employment and retirement is changing dramatically in industrialized societies, with a decreasing proportion of working life being spent in stable career progression. Many who retire from long-service career jobs now seek paid employment in bridge jobs before completely exiting the labor force. There is little research about the effects of employment transitions and instability in later life on health, but limited research on instability early in the working life does show a strong and significant relationship. Instability is found to be associated with adverse health effects, with variability by gender and type of health measure. In addition, both objective and subjective transition characteristics are related to variability in health. In this regard, this paper will explore on different aspects related to retirement, issues like, countering aging population, philosophical concern on retirement, support to retirees and variables associated with retirement. A voluntary separation occurs when an employee separates from employment due to resignation, retirement or job abandonment. Retirees commonly face four risks that can threaten to derail their retirement: work life initiatives, health care, sequence of returns, and financial status. These risks pose a multifaceted challenge that requires a combination of strategies, such as carefully choosing when to claim Social Security, allocating assets to lifetime income annuities, adopting a systematic withdrawal strategy, and planning for long-term care. This article offers a range of ideas and insights to help organizations offer the best support to retirees so that they can achieve a more secure retirement.